2020
DOI: 10.3390/cells9112528
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Osteopontin and Furin in Worsening Disease Outcomes in COVID-19 Patients with Pre-Existing Diabetes

Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused the ongoing coronavirus disease 2019 (COVID-19) pandemic, with more than 50 million cases reported globally. Findings have consistently identified an increased severity of SARS-CoV-2 infection in individuals with diabetes. Osteopontin, a cytokine-like matrix-associated phosphoglycoprotein, is elevated in diabetes and drives the expression of furin, a proprotein convertase implicated in the proteolytic processing and activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 93 publications
0
37
0
Order By: Relevance
“…Furin is a second protease involved in S-protein priming during SARS-CoV-2 infection, and also has a role in intracellular processing (241). Furin is present in both membrane-bound and secreted, soluble states with the latter usually associated with a variety of pathologies, such as diabetes or infection (242)(243)(244). Cheng et al recently reported that small molecule inhibitors of furin prevent SARS-CoV-2 infection as well as intracellular processing in vitro (245).…”
Section: Fibrinolysis and Serpins In Sars-cov-2 Infection And The Covid-19 Pandemicmentioning
confidence: 99%
“…Furin is a second protease involved in S-protein priming during SARS-CoV-2 infection, and also has a role in intracellular processing (241). Furin is present in both membrane-bound and secreted, soluble states with the latter usually associated with a variety of pathologies, such as diabetes or infection (242)(243)(244). Cheng et al recently reported that small molecule inhibitors of furin prevent SARS-CoV-2 infection as well as intracellular processing in vitro (245).…”
Section: Fibrinolysis and Serpins In Sars-cov-2 Infection And The Covid-19 Pandemicmentioning
confidence: 99%
“…Furin belongs to the family of type I transmembrane serine-proteases. The enzymatic activity is connected to the subtilisin-like catalytic domain [ 61 , 62 ]. The role of furin as an activator of various substrates is well investigated [ 63 ].…”
Section: The Ocular Tropism Of Sars-cov-2mentioning
confidence: 99%
“…OPN knockout mice survived longer than wild-type mice upon intranasal infection of Streptococcus pneumoniae , which indicates the detrimental effect of OPN on anti-bacterial defense in the pulmonary compartment during pneumonia [ 58 ]. During COVID-19 infection, OPN-induced furin may enhance the entry of SARS-CoV2 to target cells [ 59 ]. Furthermore, OPN levels were associated with the severity of COVID-19 infection and white blood cell numbers [ 45 ].…”
Section: Discussionmentioning
confidence: 99%